The role of NAMPT in the pathogenesis of psoriasis may be through the regulation of niacin metabolic pathway - Fanghua LIU; Shougang LIU; Zhe ZHUANG; Zeqiao ZHANG; Hang SU; Yongfeng CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To investigate the mechanisms of nicotinamide phosphoribosyl transferase (NAMPT) in the pathogenesis of psoriasis and to elucidate the effect of NAMPT on the nicotinamide adenine dinucleotide (NAD+) metabolic pathway in psoriasis. Methods Mitophagy gene and psoriasis microarray datasets were downloaded from the human autophagy gene database and GEO database to screen differentially expressed genes (DEGs) of mitophagy. Validation and assessment were performed by differential expression and receiver operating characteristic (ROC) curve analysis. LASSO and COX regression models were used to screen signature genes. Gene correlation and functional analysis were performed using Pearson and gene enrichment analysis (GSEA). Results A total of 16 differentially expressed mitophagy genes were identified in psoriasis, which all were highly expressed in psoriasis with high diagnostic value. The DEGs of mitophagy were mainly associated with NOD-like receptor signaling pathway, autophagy-animal, influenza A, chemo carcinogenic-receptor activation and lipid/atherosclerotic pathways. NAMPT was identified as a signature gene of psoriasis, mainly associated with the proteasome, pyrimidine metabolism, ubiquitin-mediated proteolysis, DNA replication, antigen processing and presentation, aminoacyl tRNA biosynthesis, cytoplasmic DNA sensing pathway, oocyte meiosis, homologous recombination and TOLL-like receptor signaling pathway. In psoriasis, NAD metabolic pathways were activated and positively correlated with NAMPT. In the NAD+ metabolic pathway, expression levels of BST1 were low and negatively correlated with NAMPT. In contrast, expression levels of PARP9 and PNP were high and positively correlated with NAMPT. Conclusions In psoriasis, NAMPT is highly expressed and NAD+ metabolic pathway is activated. Expression levels of NAMPT are positively correlated with the activity of NAD+ metabolic pathway. NAMPT may be involved in the pathogenesis of psoriasis through BST1, PARP9 and PNP in the NAD+ metabolic pathway.